Study of reproduction cycles and yield dynamics of the classical swine fever virus in PK-15 cultured cells using a fluorescent probes technique - Reshetniak, L.D.; Krasnobayev, E.A.; Novozhilova, E.V.; Zherebtsova, E.N.; Popova, G.A. (Биополимеры и клетка, 2000)
The authors have elaborated some methodological approaches necessary to solve certain biotechnological problems. This approaches permit to study the classical swine fever virus reproduction and accumulation in a swine established cell line, PK-15, the virus propagation being accompanied with no cytopathic effect. The reliable and promising fluorescent probe technique needing no previous virus adaptation and multiplication in permissive cells is successfully confirmed to be useful for such purposes.